Enhancing Workforce Adaptability Through Structured Digital Literacy Skill Set and Competency Standard: A Research and Development Study - Surono Surono (Edunity Kajian Ilmu Sosial dan Pendidikan, 2025)
The accelerating pace of digital transformation has reshaped workforce demands, requiring not only technical competence but also adaptability in digital environments. However, a persistent digital skills gap continues to hinder employability and productivity, as many educational frameworks lack structured and standardized digital literacy competencies aligned with industry expectations. To address this, the study employed a research and development approach using the Integrated Interface Model to formulate a digital literacy skill set and corresponding competency standards, which were validated through the RMCS system and focus group discussions with industry and academic experts. The results include eight competency units covering core and elective digital capabilities such as digital tool operation, information evaluation, ethical online communication, cybersecurity, e-commerce management, and digital content creation. This competency framework provides a modular and competency-based foundation to improve workforce adaptability and supports educational alignment with regional and global standards such as ASEAN MRA-TP and UNESCO CBET. The study calls for the adoption of these structured competencies into academic and vocational systems to enhance workforce readiness and future resilience in the digital economy.